POISSON REGRESSION MODELLING OF AUTOMOBILE INSURANCE USING R - Vantika, Sandy; Yudhanegara, Mokhammad Ridwan; Lestari, Karunia Eka (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Automobile insurance benefits are protecting the vehicle and minimizing customer losses. Insurance companies must provide funds to pay customer claims if a claim occurs. Insurance claims can be modelled by Poisson regression. Poisson regression is used to analyze the count data with Poisson distributed data responses. this paper, the data model of sample is automobile insurance claims from the companies in one year (in 2021) of observation which contains three types of insurance products, i.e., Total Loss Only (TLO), All Risk, and Comprehensive. The results of data analysis show that the highest number of claims comes from Comprehensive insurance products, especially if the premium value gets more extensive. In contrast, the least comes from TLO insurance products.